Genetic model of Cerro Colorado Chico prospect: A contribution to exploration on the north coast of Peru - Bazan Santa Cruz, Orlando (2022)
Cerro Colorado Chico prospect is located to the south of the Ancash region, it is characterized by the presence of brecciated siliceous bodies (POD quartz) with restricted halos of advanced argillic alteration silica-pyrophyllite-alunite and an extensive alteration silic-sericite-pyrite, breccias and bodies of hematite, hematitized horizons affecting volcanic-sedimentary rocks of the Casma Group, and distal quartz veins. For this research have been geological mapping at 1:5000 scale, ASTER image analysis, ICP-AES analysis of 208 rock samples, petrographic, mineragraphic and XRD mineralogical analysis of 14 samples and fluid inclusion analysis of 4 samples. The altered rocks show an enrichment in Au, As, Sr, Ba, V, Fe, Ni and depletion of Cu, Pb, Zn, Al, Ti, Sc, Co and Mn. Petrographic studies show up to three generations of quartz and abundant hematite, sometimes replacing magnetite molds and sometimes being replaced by limonites and dissiminations of rutile, pyrite and chalcopyrite. The fluid inclusions show mesothermal temperatures between 605° and 560° with 47.66% to 44.82% NaCl eq. and epithermal temperatures between 329 ° and 138 ° C with of 0.7% to 9.73% NaCl-eq. with complex evolution processes such as cooling, dilution, mixing and boiling. We proposed that Cerro Colorado Chico corresponds to a lithocap related to a magmatic-hydrothermal system of the IOCG type, which allows establishing new exploration perspectives on the north coast of Peru for IOCG-type deposits preserved in depth.